Semiology reading in "besiegement status" by Mahmoud Darwish - Yaseen, Malik; Balla, Fatima; AlNaasan, Saleh Hasan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This studing aims for studing the text besiegement status by Mahmoud Darwish from semiology perspective, where the poetical text at Mahmoud Darwish ـــــ principally the mentioned text ـــــ comes opened connotations, and inserts the reader to infinite worlds, as well as the text has massive quantity of symbols and denotations. So that reading the poetical experience semiology readying leads to discovering the secrets of the text and discovering secrets of some symbols because the poetical language divulges her secrets and says things that normative language doesn’t say. This studing has done – after it presented glance at symiology secking in symiology ogf the title, summed up the contation, and the symboles that refer to it, as well as studing the superficiality and profound structure, symbole, and studing the binaries, the uniformate, the repetition, and thire conotation in the text. يُحاول البحث دراسة نصّ "حالة حصار" لمحمود درويش من منظور سيميائي، وذلك لكون النّصّ الشّعري عند محمود درويش ــــ لاسيما النّصّ المذكورـــــ يَجيءُ مفتوح الدّلالات، ويُدخل القارئ في عوالم لامتناهية، إضافةً إلى احتواء النّصّ على كم هائل من الرّموز والإشارات. ولذلك فإنّ قراءة التجربة الشّعريّة قراءة سيميائيّة تقود إلى الكشف عن أسرار النّصّ، وكشف خبايا بعض الرّموز؛ كون اللّغة الشّعريّة تبوح بأسرارها، وتقول مالم تَقُلْهُ اللّغة المعياريّة. وقد حاولت هذه الدّراسة ـــــــ بعد أن قدّمت لمحة عن السيميائيّة ـــــــ أن تبحث في سيميائيّة العنوان ومجمل الدّلالات والرّموز التي تشير إليه، فضلاً عن دراسة البنية السطحيّة والعميقة والرّمز، ودراسة الثّنائيّات والتّشاكل والتّكرار، ودلالاتها في النّصّ.